2021
DOI: 10.3390/ma15010009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Biocompatible PEO Coating Growth on cp-Ti with In Situ Spectroscopic Methods

Abstract: The problem of the optimization of properties for biocompatible coatings as functional materials requires in-depth understanding of the coating formation processes; this allows for precise manufacturing of new generation implantable devices. Plasma electrolytic oxidation (PEO) opens the possibility for the design of biomimetic surfaces for better biocompatibility of titanium materials. The pulsed bipolar PEO process of cp-Ti under voltage control was investigated using joint analysis of the surface characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In recent years, the plasma electrolytic oxidation (PEO) method [ 30 ] has been used as an alternative approach to the production of ceramic coatings with high adhesion and anticorrosion properties [ 31 ]. The PEO method is based on anodic or alternating current polarization of the processed material in aqueous electrolytes at a high voltage, producing micro arc discharges that flow on the electrode surface [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the plasma electrolytic oxidation (PEO) method [ 30 ] has been used as an alternative approach to the production of ceramic coatings with high adhesion and anticorrosion properties [ 31 ]. The PEO method is based on anodic or alternating current polarization of the processed material in aqueous electrolytes at a high voltage, producing micro arc discharges that flow on the electrode surface [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of preliminary experiments to develop the method demonstrated that in order to obtain a uniform PEO coating on implants, surface pretreatment by sandblasting is required to create favorable conditions for microdischarge ignition. The formed coating consists of TiO 2 anatase (60-70%) and TiO 2 rutile (40-30%) [12].…”
Section: Resultsmentioning
confidence: 99%
“…Microcontroller system maintained the electrolyte temperature at 20±1°C. The PEO was performed with a pulsed bipolar mode, subject to stabilization of the pulse voltage [12], for 2 min. The treatment was carried out in an alkaline phosphate electrolyte with a conductivity of 15.3 mS/cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no net charge on the polymer chains, the chemical functional groups of the polymer chains play a vital role in determining the properties exhibited by such brushes. Some widely used uncharged polymer brushes are poly( N -isopropyl acrylamide) or PNIPAM, which is known for their thermos-responsive properties; 116 polyethylene oxide or PEO, known for their biocompatibility properties 117 as well as their ion-conducting properties (leveraged in fabricating solid polymer electrolytes 118 ); polypropylene oxide (PPO); 119 polydimethylsiloxane (PDMS); 120 etc. The chemical structures for the monomers of some of these different uncharged polymer chains have been provided in Fig.…”
Section: Findings From All-atom MD Simulations Of Uncharged Polymer B...mentioning
confidence: 99%